Evaluation of the shucking of certain species of scallops contaminated with domoic acid with a view to the production of edible parts meeting the safety requirements foreseen in the Union legislation. (18th August 2021) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Chipman, Kevin James; Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; Ntzani, Evangelia; et al.
Abstract: EFSA was asked by the European Commission to provide information on the levels of domoic acid (DA) in whole scallops that would ensure that levels in edible parts are below the regulatory limit after shucking. This should include five species of scallops. In addition, EFSA was asked to recommend the number of scallops to be used in an analytical sample. To address these questions, EFSA received suitable data on DA for only one scallop species, Pecten maximus, i.e. data on pooled samples of edible and non‐edible parts. A large part of the concentration levels was above the limit of quantification (LOQ) and only these data were used for the assessment. Shucking in most cases resulted in a strong decrease in the toxin levels. Statistical analysis of the data showed that levels in whole scallops should not exceed 24 mg DA/kg, 59 mg DA/kg and 127 mg DA/kg to ensure that levels in, respectively, gonads, muscle and muscle plus gonads are below the regulatory limit of 20 mg DA/kg with 99% certainty. Such an analysis was not possible for the other scallop species. In the absence of data from member states, published data of variations between scallops were used to calculate the sample size to ensure a 95% correct prediction on whether the level in scallops in an area or lot is correctly predicted to be compliant/non‐compliant. It was shown that 10 scallops per sample would be sufficient to predict with 95% certainty if DA levels in the area/lot were twofold below or above the regulatory limit for the highest reported coefficient of variance (CV) of 1.06. To predict with 95% certainty for levels between 15 and 27 mg DA/kg, a pooled sample of more than 30 scallops would have to be tested.